Modern sensors handbook (ISTE USA, 2007)
this book focuses on sensor types currently in use or having potential to be used in industrial applications. Sensors are one of the key elements in modern systems, as they determine the quality of the information that is acquired from real life and are used for production control and decision making. The global market for sensors is fast growing and the innovation rate is extremely high. A host of sensor devices are covered, including pressure sensors, flow sensors, optical sensors, temperature sensors, solid-state gyroscopes, and magnetic sensors. To make qualified, intelligent decisions, it is vitally important for system developers, system integrators, and decision makers to be familiar with the principles and properties of new sensor types